2015
DOI: 10.1111/cid.12366
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Osteogenic Differentiation and Bone Formation on Zirconia with Surface Grooves Created with Fiber Laser Irradiation

Abstract: Our results suggest that fiber laser irradiation produces adequate surface roughening of zirconia ceramics to support osseointegration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…In cynomolgus monkeys, one study observed comparable results for both materials after 56 weeks of follow-up and 20 weeks of (2015), Richardson, Klawitter, Sauer, Pruitt and Hulbert (1975), Saulacic, Erdosi, Bosshardt, Gruber and Buser (2014), Scarano, Di Carlo, Quaranta and Piattelli (2003), Schreiner, Schroeder-Boersch, Schwarz and Scheller (2002), Shon et al (2014Shon et al ( , 2015, Taniguchi, Kakura, Yamamoto, Kido and Yamazaki (2016) Review articles 18 Andreiotelli and Khol (2009b), Apratim et al (2015), Assal (2013), Bosshardt, Chappuis and Buser (2017) (2009) Studies investigating alumina dental implants 1 Nordlund, Zetterqvist and Oden (1989) Experimental studies investigating titanium implants coated with zirconia 1 Sollazzo et al (2008) loading. The authors evaluated mean values of 72.9% and 67.4%…”
Section: Monkeysmentioning
confidence: 99%
“…In cynomolgus monkeys, one study observed comparable results for both materials after 56 weeks of follow-up and 20 weeks of (2015), Richardson, Klawitter, Sauer, Pruitt and Hulbert (1975), Saulacic, Erdosi, Bosshardt, Gruber and Buser (2014), Scarano, Di Carlo, Quaranta and Piattelli (2003), Schreiner, Schroeder-Boersch, Schwarz and Scheller (2002), Shon et al (2014Shon et al ( , 2015, Taniguchi, Kakura, Yamamoto, Kido and Yamazaki (2016) Review articles 18 Andreiotelli and Khol (2009b), Apratim et al (2015), Assal (2013), Bosshardt, Chappuis and Buser (2017) (2009) Studies investigating alumina dental implants 1 Nordlund, Zetterqvist and Oden (1989) Experimental studies investigating titanium implants coated with zirconia 1 Sollazzo et al (2008) loading. The authors evaluated mean values of 72.9% and 67.4%…”
Section: Monkeysmentioning
confidence: 99%
“…These results are in agreement with a previous study that showed that cells on polished surfaces proliferated more rapidly than those on the rough surfaces, 36 but was not consistent with another study that stated that cell proliferation was significantly greater on rough zirconia surfaces than on smooth surfaces. 45 The sample discs used in this study were minimally rough, while samples from Taniguchi's study 45 were moderately rough. When performing zirconia surface roughing, it is important to achieve the minimum effective roughness without jeopardizing the mechanical properties.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, under laser treatment, the bone-implant contact ratio and removal torque on zirconia implants placed in rat tibiae were increased. It was suggested that laser irradiation produced adequate surface roughening of zirconia to support osseointegration 49) . It is noteworthy that another study showed that laser surface treatment showed positive effect on the viability of L929 cells 50) .…”
Section: Laser Irradiationmentioning
confidence: 99%